Climate Information Services for Increased Resilience and Productivity in Africa - Tesfaye, Kindie (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
First International Conference on “Transforming Food Systems through Climate Smart Agriculture (CSA)” National Convening Haramaya University October 27-28, 2022.